Indicadores de desempenho do Jardim Botânico do Rio de Janeiro - Rocha, Mônica Sousa da (2009)
This document presents the research developed to define performance indicators for the Rio de Janeiro Botanical Garden. Comprehends a bibliographical survey on enterprises evaluation, with special emphasis on the public sector, the indexes used by similar institutions and a proposal of indicators that allow measuring the Botanic Garden performance. A list of ideal indicators had been produced, followed by an analysis of the ones that can already be adopted based on the data available.